2018
DOI: 10.1089/sur.2017.235
|View full text |Cite
|
Sign up to set email alerts
|

Short-Course Antimicrobial Therapy Does Not Increase Treatment Failure Rate in Patients with Intra-Abdominal Infection Involving Fungal Organisms

Abstract: Patients with IAI involving fungal organisms randomized to a shorter course of Antimicrobial therapy had no difference in the rate of treatment failure. These results suggest that the presence of fungi in IAI may not indicate independently the need for a longer course of Antimicrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…In addition, critically ill patients with IAI involving fungal organisms randomized to a shorter course of antimicrobial therapy had no difference in the rate of treatment failure. These results suggest that the presence of fungi in IAI may not independently indicate the need for longer course of antimicrobial therapy [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, critically ill patients with IAI involving fungal organisms randomized to a shorter course of antimicrobial therapy had no difference in the rate of treatment failure. These results suggest that the presence of fungi in IAI may not independently indicate the need for longer course of antimicrobial therapy [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…13,15,20,21,23 The data from Sawyer et al Randomized controlled trial underwent post hoc analyses and were published in three additional manuscripts. 14,24,25 Those post hoc studies were not included in the quantitative analysis and one of the three studies were excluded from qualitative analysis as it looked at fungal IAI specifically. 24 The sixteen studies showed a wide range of heterogeneity (0-100%) among them.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…14,24,25 Those post hoc studies were not included in the quantitative analysis and one of the three studies were excluded from qualitative analysis as it looked at fungal IAI specifically. 24 The sixteen studies showed a wide range of heterogeneity (0-100%) among them. The sample sizes varied from 31 patients to 929 patients.…”
Section: Qualitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Há situações em que realmente há a necessidade de utilizar antimicrobianos por várias semanas como em situações de osteomielite e endocardite, porém caso seja viável o uso de antimicrobianos deve ser abreviado. Há publicações que demonstram que tratamentos mais curtos em comparação aos tratamentos mais longos são igualmente eficientes (43) (44).…”
Section: Redução Da Duração De Terapiaunclassified